1973
DOI: 10.1126/science.182.4107.53
|View full text |Cite
|
Sign up to set email alerts
|

An Atmosphere on Ganymede from Its Occultation of SAO 186800 on 7 June 1972

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. Fig. 1) south of the ,actual occultation zone and obtained negative results. The sky was of excellent photometric quality with scintillation noise below average and all equip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

1974
1974
2016
2016

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(18 citation statements)
references
References 6 publications
0
18
0
Order By: Relevance
“…Evidence for atmospheres came mainly from stellar occultations [Carlson et al, 1973 Baragiola and Bahr [1998] on the grounds of laboratory results that showed that 02 could not be retained in water ice in sufficient amounts to produce the observed absorption bands in Ganymede. Also, studies of 02 absorption band shapes and positions in the red (around 600 nm) showed that 02 had to be in the form of a solid, not a liquid or gas [Baragiola and Bahr, 1998].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence for atmospheres came mainly from stellar occultations [Carlson et al, 1973 Baragiola and Bahr [1998] on the grounds of laboratory results that showed that 02 could not be retained in water ice in sufficient amounts to produce the observed absorption bands in Ganymede. Also, studies of 02 absorption band shapes and positions in the red (around 600 nm) showed that 02 had to be in the form of a solid, not a liquid or gas [Baragiola and Bahr, 1998].…”
Section: Introductionmentioning
confidence: 99%
“…Evidence for atmospheres came mainly from stellar occultations [Carlson et al, 1973;Broadfoot et al, 1979] and from observation of optical emission from the atmosphere [Hall et al, 1995[Hall et al, , 1998 These authors proposed that 02 is formed by radiolysis induced by magnetospheric ions and that 02 is trapped in bubbles inside the surface ice. This interpretation was questioned by Vidal et al [1997] and by Baragiola and Bahr [1998] on the grounds of laboratory results that showed that 02 could not be retained in water ice in sufficient amounts to produce the observed absorption bands in Ganymede.…”
Section: Introductionmentioning
confidence: 99%
“…The inference of a possible atmosphere on Ganymede (> 10 -6 bar) from observations of a stellar occultation event (Carlson et al, 1973) suggests that frozen volatiles in equilibrium with such an atmosphere (possibly oxygen from the photolysis of water vapor as proposed by Yung and McElroy, 1975) might be found in the polar regions. Thus a range of different ices may be present in varying quantities on the outer-planet satellites.…”
Section: B Volatilesmentioning
confidence: 98%
“…For this review, we adopt a radius for this satellite of 1820 kin. On 6 June 1972, Ganymede occulted the 8th-magnitude star SAO 186800; the analysis by Carlson et al (1973) yields a radius of 2635 (+ 15, -100) kin, which we adopt for this review.…”
Section: Occultation Radii Of Io and Ganymedementioning
confidence: 99%
“…Smith and Smith (1972) use the occultation photometry to set upper limits of 0.9 • 10 -7 and 1.3 • 10 -7 for the surface partial pressure of CH 4 and N2, respectively, and slightly larger values result from a similar analysis by Bartholdi and Owen (1972). More recently, Carlson et al (1973) have reported photometric observations of an occultation of SAO 186800 by Ganymede on 7 June 1972. They indicate that the ingress and egress data show a gradual change in brightness over a period of several seconds, suggesting a pressure at the occultation level of at least 10 -6 bar.…”
Section: Atmospheresmentioning
confidence: 99%